Resilience and personal effectiveness for social workers - Greer, Jim (Principal lecturer in social work) (London Sage Publications Ltd, 2016)
This book is a straightforward guide on how to cope with the stress and pressures of today's social work environment by developing the right skills and knowledge. It will help students learn from a very early stage how to be at their best; from developing strategies to look after themselves and making the best use of supervision to the support they need to dealing with bullies and/or difficult people - all essential guidance on how to improve their health and mental well being and prepare them to manage the challenges they will face.
Stress and social work role -- The psychology of resilience -- Valuing our own health and wellbeing and improving work/life balance -- Time management -- Making effective use of new technology and new work styles to enhance practice -- Facing up to conflict, discrimination and bullying in the workplace -- Making the most of supervision and other sources of support -- Leading and following for effective and efficient practice -- Choosing mindful practice and building a resilient career.
Includes bibliographical references (pages 160-167) and index.
Keywords: Social service |x Psychological aspects